2006
DOI: 10.1210/me.2005-0241
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Signaling in Smooth Muscle Cells Is Regulated by Ligand Binding to the 177CYDMKTTC184 Sequence of the β3-Subunit of αVβ3

Abstract: The response of smooth muscle cells to IGF-I requires ligand occupancy of the alphaVbeta3 integrin. We have shown that vitronectin (Vn) is required for IGF-I-stimulated migration or proliferation, whereas the anti-alphaVbeta3 monoclonal antibody, LM609, which inhibits ligand binding, blocks responsiveness of these cells to IGF-I. The amino acids 177-184 ((177)CYDMKTTC(184)) within the extracellular domain of beta3 have been proposed to confer the ligand specificity of alphaVbeta3; therefore, we hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 22 publications
4
45
0
1
Order By: Relevance
“…We found that a 6 amino acid loop (positions 203-209) contained this site (39). An antibody to this region inhibited vitronectin binding, and prevented phosphorylation of β3 stimulated by vitronectin.…”
Section: Role Of Hyperglycemiamentioning
confidence: 80%
“…We found that a 6 amino acid loop (positions 203-209) contained this site (39). An antibody to this region inhibited vitronectin binding, and prevented phosphorylation of β3 stimulated by vitronectin.…”
Section: Role Of Hyperglycemiamentioning
confidence: 80%
“…This crossregulation involves not only association of the integrin with IGF1R (Brooks et al, 1997;Clemmons and Maile, 2005;De et al, 2003;Mira et al, 1999;Schneller et al, 1997), but also integrin-mediated control over the localization and/or activation of IGF1R signaling components or regulators, including IRS-1, SHC and SH2-domain-containing proteins, tyrosine phosphatase-2 (SHP-2) and substrate-1 (SHPS-1) (Clemmons, 2007;Clemmons and Maile, 2005;Clemmons et al, 2007;Lee and Streuli, 1999;Vuori and Ruoslahti, 1994). Indeed, IGF1R stimulation enhances the ligand-binding affinity of the avb3 integrin, with no change in receptor expression levels Maile et al, 2002), and avb3 stimulation enhances IGF1-mediated migration and proliferation (Maile et al, 2006a;Maile et al, 2006b;Xi et al, 2008). Moreover, integrin inhibition blocks IGF-stimulated migration (Clemmons et al, 1999;Doerr and Jones, 1996;KabirSalmani et al, 2003) and expression of a dominant-negative IGF1R construct inhibits MDA-MB-231 and MDA-MB-435 breast cancer cell invasion and metastasis in vitro and in vivo (Dunn et al, 1998;Sachdev et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…When SMCs are grown in 25 mmol/l glucose and then exposed to IGF-I, Shc and MAPK phosphorylation are significantly increased. In contrast, when SMCs are grown in 5 mmol/l glucose, there is no increase in Shc or MAPK phosphorylation (10).…”
mentioning
confidence: 84%
“…When SMCs grown in 5 mmol/l glucose are exposed to IGF-I, there is no increase in migration or proliferation (9). However, when glucose is increased to 25 mmol/l, IGF-I stimulates significant increases in migration and proliferation (10). Phosphorylation of Shc and subsequent activation of the mitogenactivated protein kinase (MAPK) pathway is absolutely required for the migration and proliferation of SMCs in response to IGF-I (11).…”
mentioning
confidence: 99%